Employee Perspectives on Stock Ownership: Financial Investment or Mechanism of Control? - Lawrence, French J. (Academy of Management Review, 1987)
This paper explores employee ownership as a financial investment rather than a mechanism of control. Viewed from such a perspective, relations among employee ownership, satisfaction, and desired influence are more complex than supposed. Employee owners' satisfaction with the firm and their jobs depends, in part, on their perceptions of the firm's financial performance and of the effectiveness of other employees. Dissatisfaction may increase efforts by employee owners to influence decision making.